Physico-Functional, Nutritional and Sensorial Features of Psyllium Husk Enriched Gluten-Free Oat Cookies - Khan, Rida; Shehzadi, Kanwal; Bacha, Umar; Afzal, Muhammad Naveed; Tanweer, Afifa; Nasim, Mohsina; Khan, Sania (Nurture, 2021)
Objective: Gluten-free (GF) cookies are usually deficient in dietary fibers as compared to traditional wheat cookies. So, we aimed to formulate GF cookies with different levels of psyllium husk (fiber) from oats flour. Methods: Three types of GF cookies were made; T0, T1, and T2 containing 0%, 2.5%, and 5% psyllium husk respectively. Analysis of functional properties of the dough, physicochemical and sensory characteristics of the cookies was performed. Results: Addition of 5% psyllium husk (T2) led to enhanced functional properties of dough (% swelling capacity SC =635.0±15.00, % water absorption capacity WAC =132.33±2.51, % oil absorption capacity OAC =28.00±2.00, % emulsion activity =59.93±0.25, % emulsion stability =60.23±0.25) and the most desirable spread factor (8.71±0.572). The total fiber content of T2 cookies was 19.41%. The mean sensory evaluation score for the overall acceptability of T2 cookies (6.32±1.096) was significantly (P=0.050) higher than the T1 cookies (5.49±0.785). 5% psyllium husk cookies (T2) surpassed 0% and 2.5% psyllium husk cookies in all parameters under study. Conclusion: The integration of psyllium husk into oat-based GF cookies resulted in excellent properties and acceptability and it can be added as a healthy snack option in diets of people with gluten intolerance.